Beyond the East/West Dichotomy—The Course Yoga: Theory and Practice Conveys the Benefits of an Ayurvedic Lens for Global Health. (May 2019) - Klatt, Maryanna; Moore, Katherine
The course Yoga: Theory and Practice (YTP) evolved from the realization that graduate and undergraduate academic offerings of "yoga courses" were filled beyond capacity, while students were not being exposed to the depth and breadth of what yoga has to offer as a holistic, integrative practice, nor how it grew up alongside Ayurveda. Students experientially understood the contribution that yoga practice made in their lives and sensed the health benefits it afforded. Yet, they were hungry for an understanding of the lens through which yoga emerged. YTP is an elective course within an academic minor of study, "Integrative Approaches to Health and Wellness" that provides nonwestern ways of understanding global medicine and health. The focus of YTP is to offer college students an in-depth, academic study of yoga, incorporating both scientific (reductionist), and an Ayurveda health perspective. This course is an educational innovation, translating the benefits of Ayurvedic and yogic lifestyle to a Western audience.